An appraisal of physical education instruction in the Torres High School - Casillan, Marcelo G. 1908- (1963)
An appraisal of the physical education instruction in Torres High School is presented in this study. The conditions or provisions affecting the teaching of this subject are identified and analyzed. Evidence of ineffective class management and undesirable administrative policies that work against a more effective instruction was determined. Lastly, suggestions or solutions to minimize, if not to correct, practices, conditions, and provisions that are inhibitory to the attainment of the goals set for the course are provided.
Thesis (M.Ed.)--University of the Philippines
Keywords: Torres High School, Manila; Physical education and training -- Philippines -- Manila